Talking with God: imagination, inspiration, and prayer in the age of neuroscience - Johnson, Paul E. (New approaches to the scientific study of religion, 2025)
"Talking with God examines the neuroscience of belief and belief change related to prayer. It puts forward a model based on neuroscience and theology to understand how God speaks to us individually and inspires us through the human capacities for language and imagination. Offering a fresh, integrated perspective for those who struggle with the dissonance between their experience in the physical world and a healing spiritual life, this work navigates a path to reconcile religious spirituality with science. It also sheds light on an integrated view of science and religious belief, accepting the physicality of consciousness while allowing for spirituality in the form of divine inspiration. Talking with God is an original academic contribution to the field of science and religion and an indispensable read for researchers and readers interested in the concept of belief and belief change from a neuroscientific perspective." --